2021
DOI: 10.17576/jsm-2021-5004-28
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Effects of COVID-19 Pandemic on Aquatic Environment: A Review

Abstract: In December 2019, a novel coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak was reported for the first time in Wuhan, Hubei province, China. This coronavirus has been referred as Coronavirus Disease 2019 or COVID-19 by World Health Organization (WHO). The spread of COVID-19 has become unstoppable, infecting around 93.5 million people worldwide, with the infections and deaths still increasing. Today, the entire planet has changed due to the greatest threat on the planet si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Additionally, there is a lack of information on how to properly dispose of the used face masks and gloves. This problem worsens by inadequate disposal facilities to deal with the biohazardous materials, and this is a great risk that can impact the marine environment and human health as a new form of marine pollutant that could contaminate the aquatic products [104].…”
Section: Risk Assessment Of Covid-19 On Aquatic Foods Securitymentioning
confidence: 99%
“…Additionally, there is a lack of information on how to properly dispose of the used face masks and gloves. This problem worsens by inadequate disposal facilities to deal with the biohazardous materials, and this is a great risk that can impact the marine environment and human health as a new form of marine pollutant that could contaminate the aquatic products [104].…”
Section: Risk Assessment Of Covid-19 On Aquatic Foods Securitymentioning
confidence: 99%
“…In Malaysia itself, in response to the pandemic, the government implemented the Movement Control Orders (MCO), which started from 18th March 2020, and lasted for almost 20 months. During this period, human activities were limited and restricted (Chuan et al, 2021). The MCO was anticipated to have a positive impact on the aquatic ecosystem, including coral reefs (Chuan et al, 2021;Somchuea et al, 2022).…”
Section: Original Researchmentioning
confidence: 99%
“…During this period, human activities were limited and restricted (Chuan et al, 2021). The MCO was anticipated to have a positive impact on the aquatic ecosystem, including coral reefs (Chuan et al, 2021;Somchuea et al, 2022).…”
Section: Original Researchmentioning
confidence: 99%
“…For example, 29 waterways in Malaysia ( Goi, 2020 ), Ganga River (India) ( Dutta et al, 2020 ), and Venice lagoon (Italy) ( Braga et al, 2020 ) revealed a generalised improvement in their water quality indexes (i.e., turbidity). Such water quality improvement could be related to a decrease in water acidification due to the decline in atmospheric NO 2 and CO 2, which often ends up in the water compartments, through acid rain or surface absorption ( Ong et al, 2021 , Lükewille and Alewell, 2008 ); or through the decrease in hazardous chemicals release, via industrial activities, tourism, and water-traffic ( Dutta et al, 2020 , Yunus et al, 2020 ). The reduction in water-traffic, fisheries, and tourism, also resulted in a decrease in water acoustic noise ( Thomson and Barclay, 2020 ), allowing aquatic species that rely on eco-localization (e.g., cetaceans) to reclaim habitats (as reviewed by Ong et al ( Ong et al, 2021 , Loh et al, 2021 )).…”
Section: Positive Effects Of Covid-19 Pandemic On the Environment – A Short-term Realitymentioning
confidence: 99%
“…Several studies have been addressing the effects of the COVID-19 pandemic on the environment throughout the first year, although the majority is focused on specific environmental compartments (e.g., air, water, soil, or biota) (see table 1 and references therein) or with a particular perspective (e.g., plastic pollution, chemical pollution, marine environment, virus epidemiology and persistence) (e.g., ( Ong et al, 2021 , Loh et al, 2021 , Facciolà et al, 2021 )). Therefore, this paper provides an overview of the positive and negative effects of the COVID-19 pandemic measures and related human activities on the different environmental compartments, along with an integrative discussion on the major drivers and effects in the long term, with particular emphasis on plastic pollution.…”
Section: Introductionmentioning
confidence: 99%